2016
DOI: 10.1186/s12888-016-0826-5
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation of severely mentally ill patients with and without problematic substance use before and during Assertive Community Treatment: an observational cohort study

Abstract: BackgroundCo-occurring substance use increases the risk of hospitalisation in people with severe mental illness, whereas Assertive Community Treatment (ACT) generally reduces hospitalisation in patients with severe mental illness and high inpatient service use. Because the superiority of ACT over standard services amongst patients with problematic substance use is uncertain, the present study examined inpatient service use amongst patients with and without problematic substance use in the 2 years before and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In another study [ 85 ], involuntary admission did not significantly influence outcomes in terms of BPRS scores. One study showed that including specific patient groups in ACT-teams reduced the number of involuntary inpatient days [ 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study [ 85 ], involuntary admission did not significantly influence outcomes in terms of BPRS scores. One study showed that including specific patient groups in ACT-teams reduced the number of involuntary inpatient days [ 86 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Norwegian ACT evaluation did not show a reduction in the number of admissions, but there was a significant reduction in compulsory admissions and total inpatient days. Patients with co-occurring substance abuse had significantly fewer involuntary inpatient days, despite severe problematic substance use at 2 years follow-up [ 42 ]. Although the ACT model has been criticized for being paternalistic and coercive, studies show that patients are generally more engaged and satisfied with ACT than traditional community-based services [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This rate of SUD is higher than estimates for non‐hospitalized older adults both with and without a diagnosis of a mental health disorder, suggesting that SUD may be a factor leading to higher rates of hospitalization in older‐age adults with mental illness. This is established in the general adult population, where SUD can be an aggravating factor for psychopathology and can increase the burden of medical comorbidities . A recent survey of >100 000 electronic health records estimated that the occurrence of Type 2 diabetes in individuals age 51 to 64 with SUD was 19% vs 11% for those without SUD …”
Section: Discussionmentioning
confidence: 99%
“…This is established in the general adult population, where SUD can be an aggravating factor for psychopathology and can increase the burden of medical comorbidities. 17 A recent survey of >100 000 electronic health records estimated that the occurrence of Type 2 diabetes in individuals age 51 to 64 with SUD was 19% vs 11% for those without SUD. 18 In this dataset, cocaine was the most prevalent SUD and had the largest effect on inpatient LOS.…”
Section: Discussionmentioning
confidence: 99%